Pelatihan dan Pendampingan Penyusunan Modul Ajar Berbasis Model POE2WE bagi Guru Sekolah Penggerak sebagai Peningkatan Kompetensi Guru - Vepi Apiati; Nana; Iis Lisnawati; Siska Ryane Muslim (Catimore: Jurnal Pengabdian Kepada Masyarakat, 2023)
Training is a programmed activity that can help teachers learn knowledge or skills. By learning new knowledge and skills, the work of teachers in their respective roles in the workplace will increase. One of the trainings that can be done is training and mentoring to develop teaching modules. The preparation of teaching modules must be able to answer and solve problems or difficulties in learning. There are a number of learning materials that are often difficult for students to understand or teachers find it difficult to convey. These difficulties can occur because the material is abstract, complicated, foreign, and so on. To overcome this difficulty, it is necessary to develop appropriate teaching modules. The driving school program is an effort to realize the vision of Indonesian education in realizing an advanced Indonesia that is sovereign, independent, and has personality through the creation of Pancasila Students. To realize this, it must be supported by human resources, in this case the teacher as an educator. Through training and mentoring of the POE2WE Model-Based Teaching Module for Motivating School Teachers, it is hoped that teacher competence will increase and the vision of Indonesian education can be realized.